ACC-Deaminase, Phosphate-Solubilizing Pseudomonas fluorescens Increase Phosphorus and Decrease Cadmium Concentration to Enhance Wheat Yield - Zia-ul-Hassan; S. Khokhar; I. Rajpar; N. Depar; G.M. Jamro; A.N. Shah; Q.D. Jogi; K.H. Talpur; N. Talpur; N.A. Wahocho (Journal of Basic & Applied Sciences, 2016)
Phosphorus (P) fertilization of wheat at higher dose may result in grain cadmium (Cd) accumulation. This field study envisaged yield and comparative P and Cd accumulation of wheat under different P doses, i.e. 0, 45 and 90 kg P2O5 ha-1 (P0, P45 and P90, respectively) and seed inoculation with rhizobacterial strains, i.e. no Pseudomonas fluorescens (SM0), with ACC-deaminase P. fluorescens (SM1) and with phosphate-solubilizing, ACC-deaminase P. fluorescens (SM2). The soil was non-saline, alkaline clay loam, poor in organic matter and P content. Both P nutrition and rhizobacteria positively affected wheat growth, yield and nutrient concentration. Increased 1000-grain weight (TGW), yield and P concentration of wheat was noted at P90 over P0 (24-132%) and P45 (3.7-37%), and in case of SM2 (13-57%) and SM1 (5.4-34%) over SM0, and for SM2 over SM1 (1.4 to 2.4-fold). Grain-Cd concentration decreased at P90 over P0 (34%) and P45 (17%), and at P45 over P0 (21%). It decreased over SM0 at SM2 (22%) and SM1 (8%), and over SM1 at SM2 (2.7-fold). Straw-Cd concentration decreased at P90 over P0 (25%) and P45 (18%), and over P0 at P45 (8%). It decreased over SM0 at SM2 (18%) but increased at SM1 (9%). At all P levels, SM2 was more effective over SM1 or SM0. TGW and straw-P increased for P90 interacting with SM2 over SM0 (8.6 and 29%) and SM1 (6 and 14%), and for SM1 over SM0 (2.5 and 13%). Grain- and straw-Cd decreased due to interaction of P90 with SM2 (30 and 23%) or SM1 (6 and 7%) over SM0, and for SM1 over SM0 (26% and 17%). We conclude that adequate P nutrition and seed inoculation with ACC-deaminase, phosphate-solubilizing Pseudomonas fluorescens increase growth and yield of wheat due to its increased P and decreased Cd concentration.